Adverse effects of pesticides on central auditory functions in tobacco growers. (3rd April 2017) - França, Denise Maria Vaz Romano; Bender Moreira Lacerda, Adriana; Lobato, Diolen; Ribas, Angela; Ziliotto Dias, Karin; Leroux, Tony; Fuente, Adrian
Abstract: Objective : To investigate the effects of exposure to pesticides on the central auditory functions (CAF) of Brazilian tobacco growers. Design : This was a cross-sectional study carried out between 2010 and 2012. Participants were evaluated with two behavioural procedures to investigate CAF, the random gap detection test (RGDT) and the dichotic digit test in Portuguese (DDT). Study sample : A total of 22 growers exposed to pesticides (study group) and 21 subjects who were not exposed to pesticides (control group) were selected. Results : No significant differences between groups were observed for pure-tone thresholds. A significant association between pesticide exposure and the results for RGDT and DDT was found. Significant differences between pesticide-exposed and nonexposed subjects were found for RGDT frequency average and DDT binaural average, when including age and hearing level as covariates. Age was significantly associated with RGDT frequency average, DDT left ear score, DDT binaural average and DDT right ear advantage. Hearing levels were not significantly associated with any of the test scores. The relative risk of failing the DDT and RGDT for the study group was 1.88 (95% CI: 1.10–3.20) and 1.74 (95% CI: 1.06–2.86), respectively, as compared with the control group. Conclusions : The results showed that tobacco growers exposed to pesticides exhibited signs of central auditory dysfunction characterised by decrements in temporal processing and binaural integration processes/abilities.